Clinical efficacy analysis of laparoscopic uterine artery pre-ligation combined with hysteroscopic curettage in the treatment of type II cesarean scar pregnancy - Teng, Dan; Gao, Han; Li, Yanli; Meng, Tingzhu; Shi, Xiuting; Shi, Jie (Frontiers in Medicine, 2023)
Objective To explore and evaluate the clinical therapeutic effect of laparoscopic uterine artery pre-ligation combined with hysteroscopic curettage in the treatment of type II cesarean scar pregnancy. Methods This study analyzed the clinical data of patients with cesarean scar pregnancy (CSP) in the Maternal and Child Health Hospital of Hubei Province from 2018 to 2022. A total of 134 patients with type II cesarean section were enrolled, out of which 78 patients were included in the final analysis. Treatment included either uterine artery embolization (UAE) combined with hysteroscopic curettage (n = 37 patients) or laparoscopic uterine artery pre-ligation (LUAP) combined with hysteroscopic curettage (n = 41 patients). The demographic and clinical characteristics of these two groups were recorded, and their short- and long-term complications on follow-up were compared. For patients with subsequent fertility requirements, we followed up these patients for 2 years after surgery, then collected and analyzed the compared subsequent pregnancy outcome. Results We found no significant discrepancies in the success rate of operation, length of hospital stay, and intraoperative blood loss between the two different operation modes. The cost of LUAP was significantly lower than that of UAE. Furthermore, the incidence of short-term postoperative complications such as fever and pelvic pain was lower in patients treated with LUAP than in those treated with UAE. In terms of long-term postoperative complications, the recovery time for menstruation in the LUAP group (49.81 ± 11.47) was earlier than that in the UAE group (34.90 ± 7.41) (p < 0.05). Additionally, 4.9% of patients in the LUAP group had decreased menstrual flow, while 59% of patients in the UAE group had a marked decrease in menstrual flow, and the incidence and severity of intrauterine adhesions were significantly lower in the LUAP group than in the UAE group(p < 0.05). Consistent with the aforementioned observations, patients treated with LUAP had better postoperative re-pregnancy outcomes than those treated with UAE. Conclusions Based on the findings, LUAP combined with hysteroscopic curettage is a safe and effective surgical scheme for the treatment of type II CSPs. In addition, compared with UAE, LUAP is associated with a lower surgical cost, fewer short and long-term complications, and better postoperative pregnancy outcomes. Thus, it should be widely applied in patients with type II CSPs.